Challenges to Operationalizing Sustainable Diets: Perspectives From Kenya and Vietnam - Hoey, Lesli; Khoury, Colin K.; Osiemo, Jamleck; Shires, Anna; Binge, Brenda; Duong, Thanh Thi; Jalango, Dorcas; Trinh, Huong T.; Huynh, Tuyen Thi Thanh; Judelsohn, Alex; Haan, Stef de; Heller, Martin C.; et al. (Frontiers in Sustainable Food Systems, 2021)
Despite the urgent need for comprehensive food systems strategies, the challenge lies in defining feasible, evidence-based intervention points. Too little is known about issues food systems decision-makers and other change agents are running up against, particularly in low- and middle-income countries where food systems are the most vulnerable to a growing number of intertwined crises. We look at this question through the lens of sustainable diets, a growing area of research and a concept that is the basis of over 30 sets of national guidelines that aim to simultaneously address health, economic and environmental dimensions of food systems. Based on 114 interviews carried out in Kenya and Vietnam, we examine the extent to which food systems researchers, business and project managers and policy actors are attempting to intervene in food systems in ways that mirror the concept of sustainable diets. We also consider how they are managing two key ingredients that are critical to systems-change – interdisciplinary data and cross-sector collaboration. Most stakeholders we interviewed were carrying out systems-based projects, oriented – even if not explicitly – around many of the sustainable diets domains: agriculture, livelihoods, food security/access/nutrition and/or environment. The majority faced formidable challenges with both data and collaborations, however, showing why it can be so difficult to move from normative ideals like “sustainable diets” to practical realities, regardless of the context. To support more comprehensive food systems policies and interventions, our findings suggest the need for strategies that can improve the collection and accessibility of actionable, cross-sector data, and mechanisms to overcome institutional barriers that limit collaboration.